Physical Activity and Thyroid Function: Implications for Metabolic Health and Exercise Performance - A Narrative Review - Muraszewska, Emilia; Muraszewski, Łukasz; Kwitowska , Patrycja; Ubysz , Eryk; Nieradka , Kornelia; Krakowiak , Dominika (Quality in Sport, 2026)
Background: Physical activity is a key determinant of metabolic health and may influence thyroid function through mechanisms related to energy balance, inflammation, and endocrine regulation. However, its relationship with the hypothalamic-pituitary-thyroid (HPT) axis remains unclear. Aim: To review current evidence on the association between physical activity and thyroid function, focusing on metabolic health, exercise performance, and clinical implications. Material and methods: A PubMed search of English-language studies published in the last 10 years was conducted to evaluate the effects of physical activity on thyroid function, metabolic parameters, and exercise capacity. Observational studies and meta-analyses were included. Results: Physical activity appears to influence thyroid function mainly indirectly via improvements in metabolic health and energy balance. Moderate exercise is associated with beneficial metabolic effects, whereas excessive training, especially with low energy availability, may lead to adaptive reductions in T3 levels. Direct effects on thyroid hormones remain inconsistent. Thyroid dysfunction negatively impacts exercise capacity, and patients often remain insufficiently active. Physical activity may also reduce fatigue and improve quality of life, although evidence is limited. Conclusions: The relationship between physical activity and thyroid function is multifactorial and bidirectional. Moderate activity supports metabolic health, but its direct hormonal effects remain unclear. Individualized assessment is essential, and further research is needed to clarify mechanisms and guide clinical practice.